2009
DOI: 10.2131/jts.34.327
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of human epidermal model LabCyte EPI-MODEL for in vitro skin irritation testing according to European Centre for the Validation of Alternative Methods (ECVAM)-validated protocol

Abstract: -A validation study of an in vitro skin irritation testing method using a reconstructed human skin model has been conducted by the European Centre for the Validation of Alternative Methods (ECVAM), and a protocol using EpiSkin (SkinEthic, France) has been approved. The structural and peralong with the approval. We have performed several evaluations of the new reconstructed human epiderthe ECVAM Performance Standards. We selected 19 materials (nine irritants and ten non-irritants) available in Japan as test che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(23 citation statements)
references
References 9 publications
0
23
0
Order By: Relevance
“…Furthermore, appendages of human skin critically influence water diffusion through the SC, making stable measurement of transepidermal water loss in vitro difficult (14). Reconstructed human epidermis (RHE), which is free of appendages, has been developed as an alternative to animal tests; its use is recommended for in vitro dermatological research because it shares many characteristics with normal human epidermis (15)(16)(17).…”
mentioning
confidence: 99%
“…Furthermore, appendages of human skin critically influence water diffusion through the SC, making stable measurement of transepidermal water loss in vitro difficult (14). Reconstructed human epidermis (RHE), which is free of appendages, has been developed as an alternative to animal tests; its use is recommended for in vitro dermatological research because it shares many characteristics with normal human epidermis (15)(16)(17).…”
mentioning
confidence: 99%
“…LabCyte EPI-MODEL has already been characterized in terms of its tissue structure and lipid composition under light and electron microscopy (data not shown), its barrier function, its immunohistochemistry and the reduction of MTT assays (Katoh et al, 2009). In addition, its application to in-house skin irritation tests such as for screening 1 1,2-Diaminopropane C 1 13.1 ± 1.9 26.3 ± 7.3 C 2 12.6 ± 2.4 13.0 ± 4.1 C 3 9.7 ± 2.7 27.9 ± 3.4 C 2 Acrylic acid C 1 1.9 ± 1.6 0.5 ± 0.6 C 2 4.8 ± 5.0 1.1 ± 0.9 C 3 14.5 ± 5.5 0.9 ± 0.6 C Assessment of the LabCyte EPI-MODEL for skin corrosion tests levels has been examined.…”
Section: Discussionmentioning
confidence: 99%
“…LabCyte was cultured from human epidermis cell and stratified on polyethylene terephthalate (PET) membrane (thickness: 13.6±0.9 ÎŒm, pore size: 0.4 ÎŒm) as a supporting layer. LabCyte morphologically resembles human skin 10) and consists of SC and viable epidermis (Epi) which is made up from granulocyte, stratum spinosum, and basal layer. The SC was differentiated from the viable epidermis (Epi model) and formed after two weeks cultivation; it was named SCEpi model.…”
Section: Three-dimensional Cultured Human Epidermis (Che)mentioning
confidence: 99%
“…Katoh et al reported that LabCyte can be applied to in vitro skin irritation testing according to ECVAM validated protocol. 10) In Vitro Skin Penetration Experiments To fit LabCyte (10 mm in diameter) between side-by-side in vitro diffusion cells (KH cell, volume; 5 mL, Vidrex Ltd., Fukuoka, Japan) of 9 mm in diameter, a silicone elastomer adaptor (external diameter; 22 mm, internal diameter; 8 mm, and thickness; 1 mm) was used. LabCyte sandwiched between the adapters was mounted between the KH cells and then the effective diffusion area for LabCyte was 0.50 cm 2 .…”
Section: Three-dimensional Cultured Human Epidermis (Che)mentioning
confidence: 99%